Lexical processing of morphologically complex Slovene words in a lexical decision task - Pavlič, Matic (Slovenski jezik, 2025)
This study investigates how the structure of pseudowords influences the lexical decision accuracy and response time in morphologically complex Slovene words. We tested three methods of constructing pseudowords: manual modification with preserved suffixes, manual modification with altered suffixes, and algorithmic generation with preserved suffixes, using the Wuggy application (Keuleers and Brysbaert 2010) adapted to Slovene. The pseudoword types did not differ significantly by accuracy, only by response time. However, these differences did not affect the accuracy rate or response time of existing Slovene words, suggesting that morphological complexity and manual/algorithmic construction of pseudowords are not relevant factors in lexical decision.
Keywords: lexicography; pseudowords; psevdobesede; psiholingvistika; psycholinguistics; slovaropisje; Slovenian language; slovenščina